What Do Survivors of Child Sexual Abuse Believe Will Facilitate Early Disclosure of Sexual Abuse? - Solberg, Ellen Tvedt; Halvorsen, Jorunn E.; Stige, Signe Hjelen (Frontiers in Psychiatry, 2021)
The purpose of this study was to explore what adult survivors of child sexual abuse (CSA) believe will facilitate early disclosure of sexual abuse. We conducted semi-structured interviews with 12 adult survivors of CSA aged 18 to 57 years, and analyzed the transcripts using thematic analysis with a hermeneutic-phenomenological approach. The findings highlighted the importance of adults facilitating disclosure and making it possible for survivors to tell about their experiences, but also the responsibility adults have to dare to consider the possibility of CSA when children struggle. Another important finding was the significance of conveying knowledge to enhance understanding of the complexity of CSA, including why disclosure is difficult, and to give adults the tools to understand and know what to do when they suspect CSA. The findings also have important implications for the planning and implementation of interventions to facilitate early disclosure of CSA.